Call for elimination program of Malaria among children under 5 years old living in refugee camps in eastern Democratic Republic of Congo - Amidu Alhassan; Lydia Sope Ajala; Bella Ode; Muhammad Alanjiro; Sumaira Rehman; Jones Onesime; Elie Kihanduka; Christian Tague; Kanza Farhan; Styves Banga; Excellent Rugendabanga; Alvin Manga; et al. (New Microbes and New Infections)
Malaria is a significant public health challenge in the Democratic Republic of the Congo (DR Congo), with a high prevalence and mortality rate, particularly among children under five years old. This study examines the impact of malaria in eastern DR Congo, where armed conflict and humanitarian crises have resulted in overcrowded refugee and internally displaced persons (IDP) camps, exacerbating malaria transmission. Malnutrition, limited access to healthcare, and poor living conditions makes children under the age of five particularly vulnerable. Despite attempts by organizations such as the World Health Organization and various non-governmental organizations to supply insecticide-treated bed nets and antimalarial drugs, implementation in refugee camps is impeded by war, resource constraints, and insufficient healthcare facilities. A focused elimination approach that includes integrated vector control, enhanced diagnostic access, healthcare professional training, and community engagement is critical. Surveillance and research are critical for determining malaria prevalence and resistance patterns. Effective malaria treatment in refugee camps necessitates broad strategies to protect vulnerable children and lower disease burdens.